2022
DOI: 10.3389/fpls.2022.1064232
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of stand productivity in Moso bamboo forest after strip cutting

Abstract: Strip cutting can effectively reduce the cutting cost of bamboo forests and promote the transformation and upgradation of bamboo forests through mechanization and modernization. Despite the rapid accumulation of Moso bamboo biomass, the dynamics of five years changes in stand characteristics and productivity after cutting remain unclear. This is critical for formulating efficient bamboo forest management measures. In this paper, plots with an 8 m width strip cut (SC) and respective reserved belts (RB) were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…However, in high density, increasing the height to crown base and bamboo height is a growth strategy to obtain nutrients, which may also lead to a decrease in bamboo leaf biomass. A previous study has shown that the culm, leaf and branch productivity of RB decreased over time during strip cutting in a Moso bamboo forest ( Zheng et al., 2022b ). In a high-density bamboo forest, there was a decoupling relationship between productivity and soil nutrients, and high density is an important reason for the decline in productivity ( Zheng et al., 2022b ).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, in high density, increasing the height to crown base and bamboo height is a growth strategy to obtain nutrients, which may also lead to a decrease in bamboo leaf biomass. A previous study has shown that the culm, leaf and branch productivity of RB decreased over time during strip cutting in a Moso bamboo forest ( Zheng et al., 2022b ). In a high-density bamboo forest, there was a decoupling relationship between productivity and soil nutrients, and high density is an important reason for the decline in productivity ( Zheng et al., 2022b ).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has shown that the culm, leaf and branch productivity of RB decreased over time during strip cutting in a Moso bamboo forest ( Zheng et al., 2022b ). In a high-density bamboo forest, there was a decoupling relationship between productivity and soil nutrients, and high density is an important reason for the decline in productivity ( Zheng et al., 2022b ). Furthermore, after the formation of new bamboo, the DBH and bamboo height factors remained stable, and the growth rate of dry matter accumulation decreased significantly after the growth of II “du” ( Su, 2012 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations